Экспоненциальная устойчивость движения на временной шкале при структурных возмущениях - Мартынюк, А.А. (Доповіді НАН України, 2010)
Вказано спосіб застосування прямого методу Ляпунова для дослідження експоненційної стійкості руху на часовій шкалі динамічних рівнянь при структурних збуреннях. A means to use the direct Lyapunov's method to establish sufficient conditions for the exponential stability of the trivial solution of a system of dynamic equations on a time scale under structural perturbations is indicated.